Constellations of Delirium in Contemporary Latin American Fiction - Acevedo Carvajal, Juan Manuel (2025)
Constellations of Delirium in Contemporary Latin American Fiction* is a meticulous, exhaustive, extensively documented, and theoretically grounded study of the representations of delirium in a corpus of novels from the late 20th and 21st centuries. This book draws an imaginary line between disparate literary texts that, when read through this connection, reveal an unexpected path of light that allows us to hear the voice of unknown galaxies and believe in the power of the imagination.
Keywords: Literary Delirium; Literary Constellations; Contemporary Latin American novel; Assembly; Deterritorialization